2021
DOI: 10.3389/fpsyg.2021.635957
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychological Impacts of Cooking During the COVID-19 Lockdown Period: A Qualitative Study

Abstract: This study aims to explore the positive psychological effects of culinary experiences during the COVID-19 lockdown days. Qualitative research methods adopted to provide a deeper understanding. Data was collected through a structured online survey from 30 participants in Turkey. This occurred between April 10th and June 3rd, 2020 when the strict confinement measures were applied. Content analysis was deductively applied according to the Stebbins’s Theory of Casual vs. Serious Leisure which classifies the well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 90 publications
2
18
0
3
Order By: Relevance
“…In-store grocery shopping frequency was lowest during the lockdown period and mostly done by one member of the household, but, as we had hypothesized, frequency increased after this period to resemble the 2019 pre-pandemic Canadian estimate of 1.3 grocery trips per week (17), and reports of more than one household member going grocery shopping increased after the lockdown. In addition, cooking meals at home significantly increased during the lockdown compared to the report for 2019, which also has been reported internationally in Eastern Europe and the Middle East (18,19). In line with these observations, the number of daily meals consumed was reported to be higher during lockdown periods compared to before the pandemic in an international online survey study with respondents from Europe, North-Africa, Western Asia and the Americas (20).…”
Section: Discussionsupporting
confidence: 72%
“…In-store grocery shopping frequency was lowest during the lockdown period and mostly done by one member of the household, but, as we had hypothesized, frequency increased after this period to resemble the 2019 pre-pandemic Canadian estimate of 1.3 grocery trips per week (17), and reports of more than one household member going grocery shopping increased after the lockdown. In addition, cooking meals at home significantly increased during the lockdown compared to the report for 2019, which also has been reported internationally in Eastern Europe and the Middle East (18,19). In line with these observations, the number of daily meals consumed was reported to be higher during lockdown periods compared to before the pandemic in an international online survey study with respondents from Europe, North-Africa, Western Asia and the Americas (20).…”
Section: Discussionsupporting
confidence: 72%
“…Changes in cooking habits emerged as a strong facilitator for healthier food choices. Studies worldwide have similarly reported increases in home cooking since the beginning of the pandemic (32)(33)(34)(35) . In different countries and across various age groups, the increase in home cooking has been associated with greater intake of fruits and vegetables and less consumption of processed foods and fast foods (35,36) .…”
Section: Individual-level Themesmentioning
confidence: 98%
“…Another qualitative study similarly reported that cooking reduced boredom and negative feelings related to COVID-19. The authors concluded that cooking may provide an 'escape' from pandemic-related stress (32) . Considering reported declines in home cooking in the years preceding COVID-19 (37) , nutrition educators may seize the opportunity to encourage this behaviour change among community-dwelling older adults post-pandemic.…”
Section: Individual-level Themesmentioning
confidence: 99%
“…As opposed to C-P, we presume home cooking and social meals were not only an unavoidable necessity for many participants in the HO-/ED-P, but also enriched lockdown routines by relief from boredom and possibilities for self-realization. This may not only add more healthy foods to dietary patterns but also help to psychologically adapt as qualitative studies imply [ 34 ]. Including positive emotions such as joy, happiness and their influence on eating habits into the survey, would have complemented the current assumptions, as these in particular have been associated with more openness to experiences and hedonic pleasures [ 35 ].…”
Section: Discussionmentioning
confidence: 99%